Performance of a small-scale greenhouse solar dryer for drying long peppers of Ban Khokamin Community Enterprise Loei Province, Thailand - Piwsaoad, Jagrapan (Creative Science, 2016)
This paper presents experimental performance of a small-scale greenhouse solar dryer for drying long peppers. The dryer consists of a polycarbonate sheets on a metal sheet floor. The dryer is 4.0 m in width, 1.0 m in length and 2.0 m in height. Four 15 W, DC fans powered by 40 W, PV module were used to ventilate the dryer. To investigate its performance, the dryer was used to dry ten batches of long peppers. For each batch, 10 kg of long peppers were dried in the dryer. Results obtained from the experiments showed that drying temperatures varied from 32°C to 65°C and the use of the dryer led to a considerable reduction of drying time, as compared to the open air sun drying. In addition, the quality of the product from the dryer was high-quality dried products.